2017
DOI: 10.1002/term.2620
|View full text |Cite
|
Sign up to set email alerts
|

Development of a transendothelial shuttle by macrophage modification

Abstract: i Declaration By submitting this thesis electronically, I declare that the entirety of the work contained therein is my own, original work, that I am the sole author thereof (save to the extent explicitly otherwise stated), that reproduction and publication thereof by Stellenbosch University will not infringe any third party rights and that I have not previously in its entirety or in part submitted it for obtaining any qualification. Copyright © 2016 Stellenbosch UniversityAll rights reserved Stellenbosch Univ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 74 publications
0
25
0
Order By: Relevance
“…For example, in the context of muscle inflammation, M1 macrophages have been illustrated to be the most motile, pro-inflammatory phenotype, while M2 macrophages are less likely to infiltrate tissues and associated with a relatively anti-inflammatory outcome (Arnold et al, 2007; Smith et al, 2008; Kruger et al, 2014). Our previous work on M1 macrophages (Visser and Smith, 2018) confirms the choice of this phenotype as superior for drug delivery. However, it should be noted that macrophage phenotype has a large degree of plasticity, which will have to be taken into account when designing drug delivery protocols for application in particular disease states.…”
Section: Components Of a Cell-based Delivery Systemmentioning
confidence: 53%
See 3 more Smart Citations
“…For example, in the context of muscle inflammation, M1 macrophages have been illustrated to be the most motile, pro-inflammatory phenotype, while M2 macrophages are less likely to infiltrate tissues and associated with a relatively anti-inflammatory outcome (Arnold et al, 2007; Smith et al, 2008; Kruger et al, 2014). Our previous work on M1 macrophages (Visser and Smith, 2018) confirms the choice of this phenotype as superior for drug delivery. However, it should be noted that macrophage phenotype has a large degree of plasticity, which will have to be taken into account when designing drug delivery protocols for application in particular disease states.…”
Section: Components Of a Cell-based Delivery Systemmentioning
confidence: 53%
“…Characterization of the engulfment and early maturation processes is well-established (Patki et al, 1998; Fratti et al, 2001; Vieira et al, 2002, 2003; Kinchen et al, 2008; Fairn and Grinstein, 2012) and are not discussed in more detail here, as we do not envisage a requirement for huge manipulation of this phase. Indeed, previous research by our group and others have demonstrated that macrophages readily take in a variety of purpose-designed materials and particles of varying sizes via endocytic pathways (Muthana et al, 2011; Zhao et al, 2011; Dreaden et al, 2012; Feng et al, 2014; Oh and Park, 2014; Huang et al, 2015; Miller et al, 2015; Tanei et al, 2016; Fan et al, 2018; Visser and Smith, 2018).…”
Section: Components Of a Cell-based Delivery Systemmentioning
confidence: 98%
See 2 more Smart Citations
“…A great deal of work has been done to advance the exploration of stem cell‐ECM interactions in tissue morphogenesis and homeostasis (Watt & Huck, ). Vast literatures have shown that DC scaffolds (Ott et al, ; Visser & Smith, ) can influence the hebavior of BMSCs and induce that BMSCs differentiate into various epithelial cell types (Krause et al, ). Herein, we demonstrate that with the DC nail bed scaffolds, the proliferation and migration of BMSCs were enhanced significantly.…”
Section: Discussionmentioning
confidence: 99%